Reminiscences, the French in India - Indian National Trust for Art and Cultural Heritage.; France. (French in India, 1997)
Contributed articles on role played by certain Frenchmen in India in the 18th century and first half of the 19th century.
Includes bibliographical references (p. [141]-143).
Contributed articles on role played by certain Frenchmen in India in the 18th century and first half of the 19th century.
Keywords: India / Civilization / 19th century.; India / Civilization / 18th century.; India / Civilization / French influences.